Diary of a wimpy kid : the meltdown - Kinney, Jeff (2018)
When snow closes Greg Heffley's middle school, he and his best friend, Rowley Jefferson, face a fight for survival as warring gangs turn the neighborhood into a wintry battlefield.
8-12
Keywords: Diaries -- Fiction; Snow -- Fiction; Winter -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Humorous stories; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Comics & Graphic Novels / General